Just Between Us Did the Love Affair Maim You Too? A Study in Female Reclamation - Winchester, Daniel (My University, 2023)
The rise of the “Female Gaze” in cinema as a means of retelling and reframing female stories within literature has become an important response to study. The female gaze uses three primary viewpoints: the individual filming, the viewer, and the character(s) present on screen. Through a combination of feminist and film theories, I argue that the female gaze has allowed for a more complex, nuanced, and accurate understanding of past works within modern storytelling. This thesis focuses on director Rebecca Hall’s 2021 film, Passing, and Apple TV’s series, Dickinson, to tie together the idea of using the female gaze to reclaim narratives, spaces, and discussions. In Dickinson’s case, the series re-examines the life of Emily Dickinson, labeling her as a war poet for the first time in American history. In Passing’s case, the film re-examines the relationship between the two central characters (Irene and Clare), labeling Clare as a hunter instead of a victim. In general, the purpose of this thesis is to examine a rising literary movement within modern media, exploring how this movement reworks older literature and contemporizes it.
Keywords: English literature; Film studies; Academic theses